Composite shear bond strength to dry and wet enamel with three self-etch adhesives - Shafiee F; Motamedi M; Zargham S (Tehran University of Medical Sciences, 2006)
Background and Aim: The bonding mechanisms of self etching primers, based upon the simultaneous etching and priming of dentin, simplifies the bonding technique, but the efficiency of these systems is still controversial. This study compared the shear bond strength of three self etch adhesive systems in dry and wet conditions. Materials and Method: In this experimental study, 77 intact bovine lower incisors with flat 600 grit sanded enamel surface were fixed in acrylic molds and divided into 7 groups, of 11 teeth. The enamel surfaces were treated according to a special procedure as follows: Group 1: Prompt L-Pop (PLP) in dry condition, Group 2: Prompt L-Pop in wet condition, Group 3: Clearfield SE Bond (CSEB) in dry condition, Group 4: Clearfield SE Bond in wet condition, Group 5: iBond (iB) in dry condition, Group 6: iBond in wet condition, Group 7: Margin Bond (Control) in dry condition. Surfaces were air dried for ten seconds, or blot dried in wet condition. Composite resin was bonded on the enamel and built up by applying a cylindric teflon split mold (4 mm height 2mm diameter). After 24 hours storage in dionized water at room temperature, all specimens were thermocycled and shear bond test was employed by a universal testing machine (Instron) with a cross-head speed of 1mm/min. The shear bond strength was recorded in MPa and data were analyzed with ANOVA and Scheffe statistical tests. P<0.05 was considered as statistically significant. The mode of failure was examined under a stereomicroscope. Results: 1- Shear bond strength of CSEB in dry condition (21.5 ± 4.8 MPa) was significantly higher than PLP and iB groups (p<0.0001). 2- Shear bond strength of iB and PLP groups in dry condition (9.60 ± 2.2, 9.49 ± 3 MPa) were significantly lower than CSEB and control (2.99 ± 5.1 MPa) (P<0.0001). 3- There was no significant difference between PLP and iB groups in dry condition (P=1). 4- Shear bond strength of CSEB in wet condition (21.8 ± 3 MPa) was significantly higher than PLP and iB groups (P=0.0). 5- Shear bond strength of CSEB (10.8 ± 3 MPa) and PLP (10.6 ± 4 MPa) in wet condition were significantly lower than CSEB and Control groups (P=0.0). 6- There was no significant difference between PLP and iB groups in wet condition (P=0.99). 7- Shear bond strength of the three adhesives had no significant difference in dry and wet conditions (PLP: P= 0.53, CSEB: P= 0.84, iB: P= 0.53). The mode of failure in two groups of PLP and two groups of iB was predominantly in the adhesive bond and in the two groups of CSEB, mixed failure (adhesive with cohesive in composite) was predominantly observed. Conclusion: CSEB had higher while iB and PLP showed lower bond strength to ground enamel. The three self-etch adhesives in this study did not show technique sensitivity to wet and dry enamel.